Impact of crowd support on home advantage in highly attended European professional football teams: a comparison between pre-, during, and post-COVID-19 periods - Leite, W.; Diniz da Silva, C.; Almeida, C. H. (International Journal of Sport and Exercise Psychology, 2025)
Recent research on home advantage (HA) in professional football leagues during the COVID-19 pandemic has yielded conflicting findings, prompting further examination of the impact of social support elimination on teams accustomed to packed stadiums. We analysed HA changes among the 51 European teams with the highest average attendance per match over the past five seasons: two pre-pandemic (2017/18, 2018/19), one pandemic (2020/21) without crowd support, and two post-pandemic seasons (2021/22, 2022/23). Employing four linear mixed models (teams as a random factor) - two encompassing teams across different league tiers ("all teams") and two focusing solely on "top-tier teams" - we found a significant negative correlation between team ability and HA, with each unit increase in team ability associated with a 0.12% to 0.15% reduction in HA. Specifically, top-tier teams experienced a notable 7% decrease in HA during the COVID-19 period (p < .05). Our analysis also underscored the explanatory power of crowd density, positively influencing HA changes for all teams. This study suggests that HA fluctuations during COVID-19 were partially related to team ability rather than crowd absence in stadiums, implying that HA changes may vary depending on the team. Practitioners and sports organisations can use these findings to gauge the magnitude of HA in specific contexts, while considering variations in team ability. This insight facilitates informed decision-making regarding match preparation, training programmes, structure regulations, and marketing strategies. Future research should pay close attention to sample selection, as minor modifications can have substantial implications for understanding the crowd support effect on HA.